History of mild traumatic brain injury is associated with deficits in relational memory, reduced hippocampal volume, and less neural activity later in life - Monti, Jim M.; Voss, Michelle W.; Pence, Ari; McAuley, Edward; Kramer, Arthur F.; Cohen, Neal J. (Frontiers in Aging Neuroscience, 2013)
Evidence suggests that a history of head trauma is associated with memory deficits later in life. The majority of previous research has focused on moderate-to-severe traumatic brain injury (TBI), but recent evidence suggests that even a mild TBI (mTBI) can interact with the aging process and produce reductions in memory performance. This study examined the association of mTBI with memory and the brain by comparing young and middle-aged adults who have had mTBI in their recent (several years ago) and remote (several decades ago) past, respectively, with control subjects on a face-scene relational memory paradigm while they underwent functional magnetic resonance imaging. Hippocampal volumes were also examined from high-resolution structural images. Results indicated middle-aged adults with a head injury in their remote past had impaired memory compared to gender, age, and education matched control participants, consistent with previous results in the study of memory, aging, and TBI. The present findings extended previous results by demonstrating that these individuals also had smaller bilateral hippocampi, and had reduced neural activity during memory performance in cortical regions important for memory retrieval. These results indicate that a history of mTBI may be one of the many factors that negatively influence cognitive and brain health in aging.